Resources are not everything, and what is a household? A critique of common approaches to analyzing livelihoods - Geiselhart, Klaus (African Geographical Review, 2016)
Studies on livelihoods have frequently focused on the household, surveying the assets available to households as the means of their subsistence. However, such studies make two assumptions which must be critically questioned: first, that those people who live in a house by nature are interested in developing a collaborative economic unit with their cohabitees; and second, that all the resources available to the household are in fact made use of. Neither of these assumptions can be taken as indisputably given. The economic cooperation of individuals is strongly shaped by cultural values, although these values often dissolve in the face of growing individualism. Further factors of societal transformation make traditional economic activities appear unprofitable or unattractive, with no successfully proven alternatives having been handed down. Individuals react in varying ways to the factors that influence these transformations. A wide range of attitudes to life has emerged, which often lead to the disintegration of traditional household structures. Most geographical research in many sub-Saharan African livelihoods contexts has yet to take these transformations into account.
Keywords: Livelihoods; household; resources; economic collaboration